Optimising PCI by Intracoronary Image-guidance - Alasnag, Mirvat; Ahmed, Waqar; Al-Bawardy, Rasha; Shammeri, Owayed Al; Biswas, Sinjini; Johnson, Thomas W. (Frontiers in Cardiovascular Medicine, 2022)
Evidence to support the use of intracoronary imaging (ICI) in guiding percutaneous coronary intervention (PCI) is growing, with observational and randomised controlled trials demonstrating a benefit in acute procedural and clinical outcomes. ICI provides an opportunity to guide PCI, detailing the nature of the coronary disease, potentially influencing lesion preparation and stent selection. Following stent deployment, ICI offers a detailed assessment of lesion coverage, associated vessel trauma and stent expansion. Consensus statements have emphasized the role of ICI and detailed the parameters of stent optimisation. However, intracoronary imaging is not adopted widely yet. Significant global differences in the uptake of ICI have been reported, with the vast majority of PCI being angiographically-guided. The three major barriers to the implementation of ICI include, in order of impact, prohibitive cost, prolongation of procedure time and local regulatory issues for use. However, it is our belief that a lack of education and the associated challenges of ICI interpretation provide the greatest barrier to adoption. We hope that this review of the role of ICI in PCI optimisation will provide a platform for PCI operators to gain confidence in the utilisation of ICI to enhance outcomes for their patients.